Estratégias metodológicas de formação continuada de professoras da educação infantil em um núcleo de estudos das relações étnico-raciais de Belo Horizonte/MG - Adriana Bom Sucesso Gomes (2022)
This research aimed to identify and understand the methodologies strategies used by the Center for Studies of Ethnic-Racial Relations of the East Region, belonging to the Municipal Education Network of Belo Horizonte/MG. We sought to understand the expressive participation of early childhood education teachers in training promoted by the East Regional Studies Center, in addition to strengthening and expanding discussions on the education of ethnic-racial relations in shared management format as a strategy of continuing teacher education. It is in the context of Belo Horizonte of effervescence of government policies thought about the promotion of racial equality, that this research is part of and becomes relevant within the university and beyond. The novelty and contributions of the study to the fields of teacher education, childhood/early childhood education and ethnic-racial relations are strengths of the work. The theoretical framework is based on categories such as ethnic-racial relations, race and racism (FAZZI, 2012; TRINIDAD, 2011; OLIVEIRA, L., 2018; ALMEIDA, S., 2019; GOMES, 2017; MUNANGA, 2005); conceptions of children and childhoods (ARROYO; 2012; COUTINHO, 2016; GOUVEIA AND SARMENTO, 2008; KRAMER, 2015); and teacher training: (ABRAMOWICZ, 2010; GOMES AND SILVA 2015; ROSEMBERG, 2011). The research subjects were early childhood education teachers participating in the Nucleus between the years 2017/2020. The participants' participation was voluntary and the selection had as criteria: frequency and participation of teachers in training meetings; development of pedagogical practices aimed at the education of ethnic-racial relations with children; length of stay and participation in the Study Center of the East Regional and representatives of teachers of the network itself and partner. The research was qualitative in nature, covering three phases: the first exploratory nature; the second immersion in the field with the application of questionnaires, interviews, informal conversations and documentary analysis; the last phase dealt with the writing of the dissertation and the educational resource. The study sought an intersectional approach to the categories of analysis such as childhood and race with a focus on teacher education. The categories of gender, race and class were also used to understand the teaching condition. Among the results, we highlight the knowledge and knowledge that emerge from the formative practices experienced. In this process, Brazilian Africanities were highlighted and guided the training strategies. The collected data indicated understandings, expectations and demands of teachers in relation to the work of ethnic-racial relations in Early Childhood Education. The contributions of training meetings at the personal and professional level were analyzed. Among the strategies that were most significant for the teachers surveyed, the following stand out: the reports of life and pedagogical practices of the participants; the conversation wheels; the repertoire of afro-Brazilian arts, work with literature, field experiences, among others. All this is part of the training curriculum in line with laws 10.639/03, 11.645/08 and DCNERER. Collective and collaborative work as principles of organization of network-structured teacher training was also part of the results found. This dissertation in e-book format composes the educational resource socialized with the Center for Studies of the East Regional and other interested parties.